Acidente botrópico em paciente pediátrico: relato de caso - Karoline Silva Zeni; Aline Campani Rodrigues; Camila Cé de Souza; Diego Gonçalves Mastella; Guilherme Michelon; Rafaela Dahlke; Leticia Fortkamp de Almeida; Fabiana Stradiotto Sartor (Sociedade Brasileira de Pediatria, 2023)
Botropic accidents are the most common among snake accidents in Brazil. The species Bothrops jararaca, the popular jararaca, predominantly inhabits the south and southeast regions, and thus is the most relevant venomous snake in the region, being responsible for most accidents. Its poison causes important clinical repercussions, with proteolytic, coagulant and hemorrhagic actions, which cause an exuberant clinical picture. In addition to the pain, local manifestations and coagulation disorders, the jararaca sting can present complications such as infections and tissue necrosis. Thus, this case report aims to describe the approach and evolution of a botropic accident involving a previously healthy 5-year-old pediatric patient.